Functional Molecules in Locally-Adapted Crops: The Case Study of Tomatoes, Onions, and Sweet Cherry Fruits From Tuscany in Italy - Berni, Roberto; Romi, Marco; Cantini, Claudio; Hausman, Jean-Francois; Guerriero, Gea; Cai, Giampiero (Frontiers in Plant Science, 2019)
The human diet is characterized by highly energetic molecules, but it also requires non-energetic compounds that are equally useful for cell functioning and for preserving organism health status. These “functional” molecules are represented by a wide variety of plant secondary metabolites, such as antioxidants, vitamins and polyphenols. Widespread commercial crops varieties contain scarce levels of functional molecules, because they have been mostly selected for productivity rather than for the content of secondary metabolites. Different scenarios (global economic situation, foreseeable environmental changes) are pushing farmers to review the use of high yield crops and to focus on the valorization of locally-adapted plants. This renewed interest in autochthonous varieties is strengthened by the growing need of consumers for functional foods with beneficial effects on human health and by the willingness to promote sustainable low-input agricultural practices exploiting local climate, soil, water and (micro)biota. Here, we want to discuss a specific case study concerning locally-adapted crops in Tuscany (Italy). Analyses of nutraceutical molecules in local crop varieties (namely tomatoes, cherries and onions) have shown that local varieties are characterized by substantially higher functional molecule contents. Our goal is to promote the high-throughput study of local varieties to understand, in a medium-term perspective, whether the cultivation of local plants is a valuable support for the diet and an adequate local economic resource. Such plants can provide a boost to the regional economy, by diversifying the local crop-market landscape. We also want to valorize the local agrobiodiversity in diversification of current crop market.